Analysis of A Government – Owned Airline’s Organizational Culture in Improving Flight Services - Prihandini, Diana; Marjuan, Ricky; Krishantoro, Krishantoro (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to determine and analyze organizational culture at PT Garuda Indonesia. This was motivated by several problems related to the services provided during flights by passengers up to the Ombudsman. This research used qualitative methods and was conducted with several informants in positions as Aircrew, management and expert informants. This research was conducted at PT Garuda Indonesia for 5 months, namely from November to March. The results of this research are that the organizational culture at Garuda Indonesia airline has been implemented quite well. This shows that the organizational culture at Garuda Indonesia has provided or provided a sense of identity for the Aircrew. The organizational culture also creates an Aircrew commitment to remain committed to the organization's mission, particularly to high standards of safety and customer-oriented service delivered by professional and dedicated employees. Garuda Indonesia's organizational culture is also capable of guiding the words and actions of its employees, as well as making it clear what they should do and say in certain situations. However, there are two organizational culture factors that become obstacles in improving the quality of Aircrew services at Garuda Indonesia, namely: a) dynamic regulations in the Flight Attendant Service Guide Book (FASGB); b) Employees who find it difficult to adapt to regulatory updates. The solution to facing obstacles in improving the quality of aircrew services at Garuda Indonesia through organizational culture is: a) Regular socialization; and, b) Enforce more strictly regarding rewards and punishment.